Low latency vision-based control for robotics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Mechatronics at Massey University, Manawatu, New Zealand - Lues, Joshua (Massey University, 2018)
In this work, the problem of controlling a high-speed dynamic tracking and interception system using computer vision as the measurement unit was explored. High-speed control systems alone present many challenges, and these challenges are compounded when combined with the high volume of data processing required by computer vision systems. A semi-automated foosball table was chosen as the test-bed system because it combines all the challenges associated with a vision-based control system into a single platform. While computer vision is extremely useful and can solve many problems, it can also introduce many problems such as latency, the need for lens and spatial calibration, potentially high power consumption, and high cost. The objective of this work is to explore how to implement computer vision as the measurement unit in a high-speed controller, while minimising latencies caused by the vision itself, communication interfaces, data processing/strategy, instruction execution, and actuator control. Another objective was to implement the solution in one low-latency, low power, low cost embedded system. A field programmable gate array (FPGA) system on chip (SoC), which combines programmable digital logic with a dual core ARM processor (HPS) on the same chip, was hypothesised to be capable of running the described vision-based control system. The FPGA was used to perform streamed image pre-processing, concurrent stepper motor control and provide communication channels for user input, while the HPS performed the lens distortion mapping, intercept calculation and “strategy” control tasks, as well as controlling overall function of the system. Individual vision systems were compared for latency performance. Interception performance of the semi-automated foosball table was then tested for straight, moderate-speed shots with limited view time, and latency was artificially added to the system and the interception results for the same, centre-field shot tested with a variety of different added latencies. The FPGA based system performed the best in both steady-state latency, and novel event detection latency tests. The developed stepper motor control modules performed well in terms of speed, smoothness, resource consumption, and versatility. They are capable of constant velocity, constant acceleration and variable acceleration profiles, as well as being completely parameterisable. The interception modules on the foosball table achieved a 100% interception rate, with a confidence interval of 95%, and reliability of 98.4%. As artificial latency was added to the system, the performance dropped in terms of overall number of successful intercepts. The decrease in performance was roughly linear with a 60% in reduction in performance caused by 100 ms of added latency. Performance dropped to 0% successful intercepts when 166 ms of latency was added. The implications of this work are that FPGA SoC technology may, in future, enable computer vision to be used as a general purpose, high-speed measurement system for a wide variety of control problems.
Keywords: Automatic control; Computer vision; Robotics